2017
DOI: 10.3390/rs9101026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Light Pollution and the Causing Factors in China’s Protected Areas, 1992–2012

Abstract: Abstract:The natural nighttime light environment of the earth has been significantly transformed by human activities. Such "light pollution" has a profound influence on ecosystems. Protected areas (PAs) play key ecological functions and are only effective at low light pollution levels or without any light pollution. In China, with rapid population growth and high urbanization rates, light pollution in PAs continues to aggravate and threaten a number of ecosystems. We used calibrated nighttime light images to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Although the wide use of artificial light at night has brought significant convenience to humankind, the dramatic change of the NTL environment inevitably affects both the ecosystem and human life, known as "light pollution" [177]. NTL data have brought new opportunities for light pollution studies, enabling evaluation over large areas with low costs compared to the traditional ground-based observations and laboratory studies [178,179]. Currently, studies of light pollution based on satellite-derived NTL data mainly lie in three aspects: (1) Characterizing and surveying the distribution of light pollution; (2) revealing the impacts of NTLs on ecological environment and species; and (3) estimating the impact on human health brought by artificial light at night.…”
Section: Light Pollution and Associated Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the wide use of artificial light at night has brought significant convenience to humankind, the dramatic change of the NTL environment inevitably affects both the ecosystem and human life, known as "light pollution" [177]. NTL data have brought new opportunities for light pollution studies, enabling evaluation over large areas with low costs compared to the traditional ground-based observations and laboratory studies [178,179]. Currently, studies of light pollution based on satellite-derived NTL data mainly lie in three aspects: (1) Characterizing and surveying the distribution of light pollution; (2) revealing the impacts of NTLs on ecological environment and species; and (3) estimating the impact on human health brought by artificial light at night.…”
Section: Light Pollution and Associated Effectsmentioning
confidence: 99%
“…Widespread studies have been conducted to characterize the distribution of light pollution from local [68,[180][181][182], national [183][184][185], regional [186], and global scales [187,188] using various NTL datasets derived from different sensors. The distribution of light pollution in both developed areas, such as Europe [181,182,186], and fast developing areas, such as China [13,68,179,183,184] and Pakistan [185], have been investigated using the time series of NTL data from the DMSP-OLS. Necessary data preprocessing has been performed for consistent and comparable light pollution mapping.…”
Section: Light Pollution and Associated Effectsmentioning
confidence: 99%
“…In addition, NTL provides a new opportunity for estimating energy consumption and greenhouse gas emissions [8][9][10][11]. It also promotes research on the distribution of light pollution and its impact on human health and protected areas [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the invention of electric lights, a variety of artificial light sources have illuminated the night sky, providing great convenience for the lives and productivity of humans. With the development of lighting technology and the economy, artificial light has continuously increased across the world, both in intensity and extent [1][2][3]. Kyba et al indicated that Earth's artificially lit area grew by 2.2% per year during the period of 2012-2016 based on NPP/VIIRS nighttime light remote sensing data [4].…”
Section: Introductionmentioning
confidence: 99%